An Investigation Into Best Practices and Lessons Learnt With Respect to China's Crackdown on Corruption - Kwok, Dominic (2018)
Corruption is a well-documented problem in China, as well as many other developed and undeveloped countries across the world. The problem is particularly pronounced in countries that have undergone rapid economic transformation, allowing large amounts of wealth to fall into the hands of a select few individuals. Although corruption has been researched extensively, what is less covered are potential solutions that the country, and others looking to carry out similar reform, could use to combat corruption most effectively. As China has transitioned from a planned economy to a market economy, and the economy has become more powerful than ever, corruption is increasingly seen as one of the largest barriers to its sustained economic growth. The purpose of this paper is to provide a recommendation to China, which highlights some of the ways that China can most effectively tackle the problem of corruption by analyzing the anti-corruptive measures that other countries, such as Hong Kong, have effectively executed